Soil- moisture and temperature from the PhytOakmeter plot DKr (Kreinitz, Germany) from 2023 - Marie-Lara Bouffaud; Sylvie Herrmann; Paul Remmler (PANGAEA, 2025)
As part of PhytOakmeter (www.phytoakmeter.de), time-domain transmission, soil moisture and -temperature sensors with custom-made logger systems were used to measure time series of soil state variables. The aim of these investigations was to provide data on environmental properties used in a cross-disciplinary approach. The measurement device consisted of two sensors at three different depths. The dataset contains the values of time (UTC), relative permittivity, soil moisture (in % vol) derived from permittivity and soil temperature (in °C). Determination of soil moisture was done using the formula of Topp et al. (1980). As sensors, the SMT100 soil moisture sensors with integrated temperature measurement were used. All sensors were installed within the upper 50cm below ground. The exact depths for each sensor are listed in the dataset and parameter comment.
In: Herrmann, Sylvie; Bouffaud, Marie-Lara (2025): Soil texture, soil physicochemical properties and climatic data from the PhytOakmeter plot DKr (Kreinitz, Germany) [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.982540